Automated inflammatory bowel disease detection using wearable bowel sound event spotting - Baronetto, Annalisa; Fischer, Sarah; Neurath, Markus; Amft, Oliver (Frontiers in Digital Health, 2025)
Introduction: Inflammatory bowel disorders may result in abnormal Bowel Sound (BS) characteristics during auscultation. We employ pattern spotting to detect rare bowel BS events in continuous abdominal recordings using a smart T-shirt with embedded miniaturised microphones. Subsequently, we investigate the clinical relevance of BS spotting in a classification task to distinguish patients diagnosed with inflammatory bowel disease (IBD) and healthy controls. Methods: Abdominal recordings were obtained from 24 patients with IBD with varying disease activity and 21 healthy controls across different digestive phases. In total, approximately 281 h of audio data were inspected by expert raters and thereof 136 h were manually annotated for BS events. A deep-learning-based audio pattern spotting algorithm was trained to retrieve BS events. Subsequently, features were extracted around detected BS events and a Gradient Boosting Classifier was trained to classify patients with IBD vs. healthy controls. We further explored classification window size, feature relevance, and the link between BS-based IBD classification performance and IBD activity. Results: Stratified group K-fold cross-validation experiments yielded a mean area under the receiver operating characteristic curve ≥0.83 regardless of whether BS were manually annotated or detected by the BS spotting algorithm. Discussion: Automated BS retrieval and our BS event classification approach have the potential to support diagnosis and treatment of patients with IBD.
CRIS-Team Scopus Importer:2025-04-11
Keywords: bowel sound; digestion monitoring; inflammatory bowel disease; machine learning; ubiquitous computing